ANALISIS BAURAN KOMUNIKASI PEMASARAN LOKA PADANG DALAM MENINGKATKAN PENJUALAN PADA MASA PANDEMI COVID-19 - Datuk Muhammad Andy Syahputra (2023)
The Covid-19 pandemic has become a very difficult time for marketing activities in all business fields. The Covid-19 pandemic hampered marketing activities, which resulted in a decrease in sales. Loka Padang is one of the businesses in the food sector that experienced a decline in sales during the Covid-19 pandemic. This research was conducted to find out the marketing communication mix used by Loka Padang during the Covid-19 pandemic. The implementation of the communication mix was carried out as a step in overcoming the problem of declining sales of Loka Padang that occurred during the Covid-19 pandemic. In this research, the writer uses marketing communication theory. The research method used in this study is a qualitative method with a type of qualitative descriptive research through interviews, observation and documentation. The results of the study stated that there was a marketing communication mix implemented by Loka Padang through the "BerbagiLoka" campaign to increase sales turnover during the Covid-19 pandemic. The marketing communication mix has a very important role in increasing Loka Padang sales during the Covid-19 pandemic. In addition, the use of social media also has a positive impact on the overall marketing communications carried out by Loka Padang. Social media greatly provides easy access in carrying out marketing communications with a wider reach during the Covid-19 pandemic.